Programming with Nucleus Fitting software versus Custom Sound: comparison of map characteristics and outcomes in experienced cochlear implant recipients...15th International Conference on Cochlear Implants and Other Implantable Auditory Technologies; 27th Jun 2018 - 30th Jun 2018; Antwerp, Belgium - Kaplan Neeman, R.; Yaar Soffer, Y.; Yakir, Z. (Journal of Hearing Science, 2018)
Accurate programming is essential in order to maximize the benefits from cochlear implants (CI), is dependent on clinician's knowledge and skills, and is a time consuming process. In face of the increasing numbers of CI recipients, and the subsequent growing demand for CI clinical care, Cochlear Ltd. created a simplified programming software, aimed at shortening and streamlining the programming process. The purpose of the present study was to compare map characteristics and outcomes in experienced CI users programmed with the new Nucleus Fitting software (NFS) and the conventional Custom Sound software (CS). Participants were twelve postlingually deafened adults, 42 -75 years old, implanted with Cochlear Freedom or Profile implants. Map minimum and maximum levels, aided thresholds, speech perception outcomes, and the speech, spatial and qualities of hearing scale (SSQ) were compared between CI recipients programmed with each software. At the first and second programming sessions, four weeks apart, CS and NFS were alternated randomly, followed by four weeks of CI use with each map. At the third session both maps were loaded on the processor and the recipient was instructed to use both and choose the preferred map. Four weeks after the third session participants reported their preference. Programming with CS versus NFS resulted in: Similar map minimum levels and marginally higher maximum levels using NFS, mainly in the apical and medial segments; Non-significant differences in aided thresholds, monosyllabic word scores, and sentence recognition in noise (0-5dB, <10%, 0.5-1dBSNR, respectively); Although SSQ results were also similar, map preferences were not uniform; 4) Programming duration with NFS was shorter by ~ 30% (4-12 minutes in over 90% of sessions). In conclusion, programming by means of NFS versus CS in experienced CI recipients did not yield significant differences in map characteristics, speech perception outcomes, and self-reported quality of hearing.